Postprandial lipemia: the origin of an early peak studied by specific dietary fatty acid intake during sequential meals. - Fielding, B; Callow, J; Owen, R; Samra, J; Matthews, D; Frayn, K (1996)
Previous studies have noted the presence of an early postprandial peak in plasma triacylglycerol concentration, particularly when successive meals have been consumed. We tested the hypothesis that fat from a previous meal contributes to this early postprandial lipemia. We investigated the effect of consuming a lunch containing 61 g fat 5 h after a breakfast containing 54 g fat. The predominant fatty acids in the first meal, expressed as % by wt of total fatty acids, were 18:2 (linoleic acid), 68%, and 18:1 (oleic acid), 19%. The main fatty acids in the second meal were 18:1 (75%) and 18:2 (8%). After lunch, the early peak (at 50-60 min) in chylomicron triacylglycerol was found to contain a large proportion of 18:2, the main constituent of the first meal, whereas at later time points the chylomicron triacylglycerol fatty acid profile more closely resembled that of the second meal. Control studies in three subjects showed the complete absence of the early peaks in plasma and chylomicron triacylglycerol concentrations when either the lunch was omitted or the first meal was low in fat. The plasma nonesterified fatty acid profile also showed a corresponding peak in 18:2 at 50-60 min, which may represent the release into the plasma of fatty acids arising from the hydrolysis of chylomicron triacylglycerol by adipose tissue lipoprotein lipase.